PSYCHOLOGICAL AND PEDAGOGICAL MECHANISM IN FOREIGN LANGUAGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article discusses the integrative nature of the subject "Foreign language", so the element of a foreign language is an integral part of the meta -subject concept of the algorithm of educational and research activities. As part of the study, a model was proposed for the development of teaching and research skills, correlating with universal learning activities, based on the study of fundamental meta -subject objects as the content of the subject "Individual educational project" and meta -subjects in a foreign language as a form of learning.